The Predictability of Anatomical Self-Efficacy Perception Levels of Associate Degree Students in Academic Performance - Horata, Erdal; Madan, Gülay (The European Research Journal, 2026)
Objective: Anatomy education is a fundamental component of health education and professional competence. Anatomical self-efficacy is defined as the belief in one's ability to successfully complete anatomy instruction. This study aimed to examine the difference in anatomical self-efficacy perception score over a semester and assess its impact on predicting the academic performance of associate degree students enrolled in gross anatomy courses.Methods: The demographic data of the students were collected. The “Self-efficacy Perception Scale for the Human Anatomy Course” was administered twice before the mid-term and final exams during the semester. As an academic performance, the mid-term and final exam grades were retrieved from the e-campus information system. Differences in exam grades and anatomical self-efficacy perception were analyzed using a t-test, while the effect of anatomical self-efficacy perception on exam grades was assessed through simple linear regression analysis.Results: The mid-term (P